BACTERIAL FLORA OF FRESH AÂ·ND ICED INDIAN MACKEREL (RASTRELLIGER KANAGURTAJ AND ITS RESPONSE TO CHLORTETRACYCLINE (CTC) TREATMENT - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2017)
Quantitative and qualitative studies on the bacterial floraof fresh Indian mackerel ( Rastrelliger kanagurta) have beenmade. The total native flora as well as 5 ppm. CTC insensitiveflora of the fish showed variations with season. About90 % of the fresh fish flora was sensitive to 5 ppm. CTC.The natural flora of the fresh fish consisted of Vibrios,Pseudomonas, Achromobacter, Flavobacterium, Corynebacteria,Micrococci, Bacillus and yeasts. In the CTC insensitive flora,Vibrios predominated followed by yeasts. The selection ofbacterial genera during storage of the fish in ice and in5 ppm. CTC incorporated ice has also been investigated. Atthe time of spoilage, Pseudomonas were found to be the dominantflora of the fish stored in both types of ice.